Dielectric properties of pure alumina from 8 GHz to 73 GHz. Issue 14 (November 2016) - Marco, D. Di; Drissi, K.; Delhote, N.; Tantot, O.; Geffroy, P.-M.; Verdeyme, S.; Chartier, T.
Abstract: This paper is focused on the impact of density, average grain size, and impurity content on dielectric properties of pure alumina (<50 ppm) from 8 to 73 GHz. To reach very low loss tangents up to high frequencies a particular attention is given to starting powders impurities, sintered densities and measurement uncertainty. Experimental protocols have also been elaborated to avoid any chemical contamination during the shaping process and to control precisely the sintering step. The dielectric performances and the most influencing factors on dielectric performances of alumina are compared and discussed with data collected in literature.